THE CHARACTERISTICS OF STRATEGIC PLANNING IN THE PROCESS OF MANAGEMENT (Intent Research Scientific Journal, 2024)
Strategic planning is the process of developing a comprehensive plan to achieve a company's goals and objectives. It serves as a foundation for managing the enterprise, bringing together all levels of the company. The strategic planning process is also the primary tool for making management decisions.